2013
DOI: 10.1162/jocn_a_00407
|View full text |Cite
|
Sign up to set email alerts
|

Look Again: Effects of Brain Images and Mind–Brain Dualism on Lay Evaluations of Research

Abstract: Brain scans have frequently been credited with uniquely seductive and persuasive qualities, leading to claims that fMRI research receives a disproportionate share of public attention and funding. It has been suggested that functional brain images are fascinating because they contradict dualist beliefs regarding the relationship between the body and the mind. Although previous research has indicated that brain images can increase judgments of an articleʼs scientific reasoning, the hypotheses that brain scans ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 33 publications
5
48
1
1
Order By: Relevance
“…On the other hand, these two societies can also be characterized by a strong prevalence of scientific rationale, which in combination may explain the variance in explicit beliefs in mind-body dualism earlier research reports (Forstmann et al, 2012;Hook & Farah, 2013;Proctor, 2008). People with different cultural or religious backgrounds-for example from societies in Asia or Africa-may very well differ in their explicit endorsement of dualistic or physicalistic statements (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these two societies can also be characterized by a strong prevalence of scientific rationale, which in combination may explain the variance in explicit beliefs in mind-body dualism earlier research reports (Forstmann et al, 2012;Hook & Farah, 2013;Proctor, 2008). People with different cultural or religious backgrounds-for example from societies in Asia or Africa-may very well differ in their explicit endorsement of dualistic or physicalistic statements (cf.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, when explicitly asked about their conceptions about the relation of minds and bodies, most adults in Western societies deny that both are entirely independent entities (Procter, 2008) and have a slight tendency to agree with strictly physicalistic rather than dualistic statements (Hook & Farah, 2013). However, as research has shown that naive theories can easily coexist with acquired scientific knowledge (Shtulman & Valcarcel, 2012), an explicit endorsement of physicalistic beliefs cannot rule out that people remain intuitive mind-body dualists at heart.…”
mentioning
confidence: 99%
“…A seminal study showed that displaying colorful renderings from brain scans, relative to simple bar graphs or plain text, led individuals to attribute more scientific merit to cognitive research (McCabe and Castel, 2008). Thereafter, however, some accounts questioned the import of these initial findings (Farah and Hook, 2013)—citing shortcomings in the original methodology and inability to replicate (Baker et al, 2013; Hook and Farah, 2013; Michael et al, 2013; Schweitzer et al, 2013). And yet, the quality of brain images may mediate their sway over critical reasoning: compared to tame graphical representations of the brain, images that were more three-dimensional and tangible increased the perceived quality of neuroscience information (Keehner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is reminiscent of the promise-disappointment cycles identified in societal expectations of biotechnology [11] and indicates that the public image of neuroscience may not be realistic, but is often positively or negatively biased. The translation of neuro-imaging research to the public and daily life applications is not straightforward and sensitive to misconceptions ([12], [13], [14]; but see [15]). For example, common myths are that we only use 10% of our brain [16], or the idea that children are either “left-brained” or “right-brained” learners [2], [12].…”
Section: Introductionmentioning
confidence: 99%